TiO2 Nanoparticles Decorated Graphene Nanoribbons for Voltammetric Determination of an Anti-HIV Drug Nevirapine - Daniel Apath; Mambo Moyo; Munyaradzi Shumba (Journal of Chemistry)
In the present study, electrochemical behavior of nevirapine on a glassy carbon electrode (GCE) modified with TiO2 nanoparticles decorated graphene nanoribbons was investigated. Characterization of different components used for modifications was achieved using Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The electrochemical behavior of nevirapine on the modified electrodes was examined using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS), chronoamperometry (CA), and differential pulse voltammetry (DPV). A considerable oxidation potential decrease of +352 mV for nevirapine in 0.1 M phosphate-buffered saline (PBS), pH 11.0, was achieved due to synergy offered by graphene nanoribbons and TiO2 compared to graphene nanoribbons (+252 mV) and TiO2 (−37 mV), all with respect to the glassy carbon electrode. Under optimized conditions, DPV gave linear calibrations over the range of 0.020–0.14 µM. The detection limit was calculated as 0.043 µM. The developed sensor was used for determination of nevirapine in a pharmaceutical formulation successfully.